Long-term predictors of mortality after percutaneous coronary intervention in the era of drug-eluting stents - Wilson, W.; Andrianopoulos, N.; Clark, D.; Duffy, S.; Brennan, A.; Harries, I.; New, G.; Sebastian, M.; Loane, P.; Reid, Christopher; Ajani, A. (2011)
The aim was to examine timing, causes, and predictors of death during long-term follow-up after contemporary percutaneous coronary intervention (PCI) using a large multicenter Australian registry. The cohort consisted of 10,682 consecutive patients from the Melbourne Interventional Group registry undergoing PCI (February 2004 through November 2009). For the first time in Australia, long-term mortality rates of a PCI cohort were defined by linkage to the National Death Index database. The cohort (mean age 64 ± 12 years) comprised 75% men, 24% diabetics, 59% with multivessel disease, 4.4% with renal failure, 25% with ST-elevation myocardial infarction (STEMI), 2.5% with cardiogenic shock, and 5.1% with heart failure. Drug-eluting stents (DES) were used in 43% of cases. Mean follow-up was 3.2 ± 0.5 years. In-hospital, 30-day, 12-month, and long-term (3.2 ± 0.5 years) mortalities were 1.6% (80% cardiac), 2.1% (79%), 3.9% (61%), and 8.2% (50%), respectively. Independent predictors of long-term mortality included age (hazard ratio 1.05, 95% confidence interval 1.04 to 1.06), cardiogenic shock (4.58, 3.60 to 5.83), renal failure (3.14, 2.58 to 3.82), previous heart failure (1.97, 1.60 to 2.41), STEMI (1.79, 1.47 to 2.18), peripheral vascular disease (1.72, 1.4 to 2.11), non-STEMI (1.58, 1.32 to 1.90), multivessel disease (1.47, 1.24 to 1.74), current smoking (1.39, 1.12 to 1.71), diabetes (1.36, 1.16 to 1.59), and cerebrovascular disease (1.33, 1.06 to 1.60, p <0.01 for all comparisons). DES deployment appeared protective against late mortality (hazard ratio 0.85, 0.73 to 0.99, p = 0.04); however, after 30 days, there was no difference in mortality rates between those who received a bare metal stent and those who received a DES. In conclusion, different clinical variables such as renal and heart failure predicted long-term mortality after PCI, whereas DES use in this large registry was not associated with late mortality risk. © 2011 Elsevier Inc. All rights reserved.